The Effect of Discipline and Motivation on Work Ethics Employee at the Office of the Election Supervisory Board (Bawaslu) of Southeast Sulawesi Province - La Ode Hamida; Arfin Bagea; Asraf Yunus (Indonesian Journal of Business, Accounting and Management (IJBAM), 2023)
This research aims to investigate the impact of discipline and motivation on employees' work ethic at the General Election Supervisory Board (Bawaslu) office in Southeast Sulawesi Province. The research objective is to enhance employees' work ethics through discipline and motivation at the Bawaslu office in Southeast Sulawesi. The study population comprises all office workers at the General Elections Supervisory Agency in Southeast Sulawesi Province. The sample size was determined to be 65 employees using the probability sampling formula. The research methodology used quantitative descriptive and multiple linear regression analysis to analyze the data. The findings reveal that both work discipline and motivation significantly and positively affect the work ethic of office employees at the General Election Supervisory Agency (Bawaslu) in Southeast Sulawesi Province, both partially and simultaneously.